Determinants of Mother to Child Transmission of HIV, at Matobo District in Matabeleland South Province in Zimbabwe from January 2021 to December 2021: A Cross-sectional Study - Ntombizike Setheli; Thabani Tawanda Dzvairo; Maibouge Tanko Mahamane Salissou (Journal of Nature and Science of Medicine, 2025)
Background: Vertical transmission of HIV is ranked as the second most common means of HIV transmission and remains a significant public health concern at Matobo district located at Matabeleland South province in Zimbabwe. Matobo district located like many other districts in Zimbabwe, continues to grapple with high mother-to-child transmission (MTCT) rates, recording an average of 3–4 cases of infant infections through MTCT every quarter based on documented sources in its District Health Information System. Despite the adoption of the B+ option at Matobo District in 2013, MTCT rates in the district have remained stagnant at 10%–14%, well above the global target of <5%. Aim and Objective: This study was a cross sectional aimed to investigate the determinants of MTCT of HIV where Materials and Method: 185 records of mother baby pairs (MBP) delivered between January 2021 and December 2021 were retrieved from the register and reviewed. A structured data collection pro forma was used to extract the data from the MBP register. Data on mother’s age, gestation age on booking, HIV status, antiretroviral therapy (ARV) status, maternal viral load, syphilis results, infants HIV status, ARV prophylaxis status, and feeding method were extracted. Result: Among the 185 mothers, 53 cases (28.6%) were HIV positive, furthermore, among the 53 HIV-positive mothers, only 6 of them have their infants tested HIV positive. This resulted in an elimination of MTCT rate of 11.3%. Significant factors associated with MTCT of HIV were the maternal viral load >1000 copies odds ratio (OR) =92.0; 95% confidence interval (CI): 6.8–1249.7; P < 0.050. A positive syphilis result in the mother was strongly associated with MTCT (OR = 21.0; 95% CI: 1.7–312.4; P < 0.050). The practice of mixed feeding among infants showed a notable association with MTCT with an OR = 45.0; 95% CI: 4.9–410.5; P < 0.050. Conclusion: These findings underscore the importance of addressing maternal viral load, syphilis screening, and infant feeding practices to mitigate the risk of HIV transmission from mother to child.